The Art of Leadership - Manning George (McGraw -Hill, 2008)
The Art of Leadership uses a highly interactive approach to explore Leadership Development. By blending behavior theory, practical application, and personalized learning, students are encouraged to develop their full potential as a leader and to become the kind of leader they always wanted to have. The book can be described as more than just a textbook. Rather, it is a "learning" book which actively involves the reader in the learning process. The text’s applied approach combines behavior theory with business practice, as each chapter focuses on central concepts and skills in an important area of leadership development. The book is made more valuable and the impact is made greater by the self-evaluation questionnaires and practical exercises that are used for personal development and class involvement. In this way, readers are equipped to engage with all that the text offers. The Art of Leadership retains the most popular topics and exercises of the previous edition and adds timely subjects and new activities to make the book fresh, alive, and interesting for leaders in today's workplace. It teaches concepts, principles, and skills of leadership in a way that is appropriate for both new and experienced leaders, as well as for the everyday person who must influence others to get things done.